The Role of Exergaming in Improving Physical Activity: A Review - Sween, Jennifer (2014)
BACKGROUND: The high prevalence of obesity in America can be attributed to inadequate energy expenditure as a result of high levels of physical inactivity. This review presents an overview of the current literature on physical activity, specifically through active videogame systems (exergaming) and how these systems can help to increase physical activity levels. METHODS: The search strategy for this review was to identify previous studies which investigated energy expenditure levels using a single active video game or a combination of active videogames. RESULTS: Based on data from 27 studies, a strong correlation exists between exergaming and increased energy expenditure (up to 300% above resting levels). The majority of active videogames tested were found to achieve physical activity levels of moderate intensity, which meet American College of Sports Medicine guidelines for health and fitness. CONCLUSIONS: Exergaming is a new and exciting strategy to potentially improve physical activity levels and reduce obesity among Americans.